On switched control of discrete-time Takagi-Sugeno fuzzy systems with unknown membership functions - Oliveira, Diogo R. de (2018)
A switched control design for a class of uncertain nonlinear discrete-time systems is proposed in this manuscript. The proposed procedure uses Takagi-Sugeno fuzzy models to describe the nonlinear systems and the membership functions can depend on immeasurable premise variables or uncertain bounded parameters. Based on a non-quadratic Lyapunov function, the design conditions are given in terms of Linear Matrix Inequalities (LMIs) and ensure asymptotic stability to the controlled system. In addition, a procedure that uses a linear time-invariant controller is presented. A theoretical analysis proves that if the LMI stability conditions for the closed-loop system with a time-invariant controller hold, then the LMI stability conditions, obtained using the switched control law, also hold. The both procedures do not use the membership functions to implement the control law. Finally, a numerical example illustrates the effectiveness of the proposed method and compares it with procedures found in the literature.